Genre-Based Approach in Writing Explanation Text: A Systematic Literature Review - Hitimala, Hardianto; Damayanti, Ika Lestari; Yusuf, Fazri Nur (Universitas Islam Sultan Agung, 2024)
This paper presents an analysis of a systematic review based on published studies on the genre-based approach (GBA) in writing explanation texts. The studies reviewed were from 2019-2023 with a total of ten studies. The objective of this review is to show how GBA enhances students’ writing skills in explanation texts, as well as the research trends related to GBA in the context of explanation texts. This review used thematic analysis to categorize the main themes that emerge in the selected studies. The findings show that the genre-based approach to writing explanation texts is very effective and enables students to understand and produce coherent, cohesive, and well-organized written works, as well as to improve their awareness and creativity skills, as they learn to examine, evaluate, and produce explanation texts, especially with the support of media or other techniques such as images, and jigsaw. These findings confirm that the genre-based approach improves students’ skills in writing explanation texts. Regarding the publication trends by year, there has been a limited number of research on GBA in the genre of explanation texts in the last 5 years, with the peak of publication in 2023 and 2020 (3 articles each), and the lowest in 2019 and 2022 (1 article each). In addition, most of the publications on this topic in the last 5 years came from Asian countries, with Indonesia leading the list, followed by Thailand.